DIALECTIC RELATIONSHIP BETWEEN THE QUR’AN AND HADITH: THE INTERPRETATION OF THE TERM “AS-SĀ‘AH” USING CRITICAL HERMENEUTIC ANALYSIS - Amir, Abdul Muiz; Syamsuddin, Sahiron; Masruri, Siswanto (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
This study aims to uncover the polemic relationship between the Qur’an and the Hadith regarding the concept of as-sā‘ah (the end of life in the world). This phenomenon was investigated using a philosophical analysis-based qualitative research design. This study uses critical hermeneutic reading to textualize and historically contextualize the articulations of the as-sā‘ah in the al-Qur’an and Hadith. The findings suggest that the polemic was sparked by a disagreement between the al-Qur’an and Hadith narrations over the meaning of as-sā‘ah. The Qur’an only mentions it in the context of eschatology, whereas some Hadith narrations include descriptions of the end times or events that occur before the Day of Judgment (apocalyptic). The impact of meaning evolution is felt not only on a conceptual level but also on a practical level. Eschatology is limited to conveying spiritual morality messages, whereas apocalyptic is more commonly used for political propaganda that is prone to instilling violent ideas in religion. This finding has ramifications for the study of the Qur’an and Hadith, particularly in the area of examining the text and historical contexts to comprehend the relationship between the Qur’an and Hadith narrations.Keywords: As-Sā‘ah; Critical Hermeneutics; The Qur’an and Hadith.الملخصأهداف هذه الدراسة الكشف عن العلاقة بين نصوص القرآن والحديث في قضية ”الساعة“ التي تؤدّي إلى الجدل. تمت دراسة هذه القضية باستخدام المنهج النوعي بناء على التحليل الفلسفي. وهذا التحليل يبنى على التأويلية النقدية لكلمة ”الساعة“ الواردة في نصوص القرآن والحديث حرفيا وسياقيا تاريخيا. تشير نتائج هذه المقالة إلى أن الجدل في معاني